BUILDING RESILIENT SECURITY SYSTEMS: THE ROLE OF AI IN DETECTION AND INCIDENT RESPONSE - Sundar Subramanian (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Understanding and implementing Artificial Intelligence in security detection and incident response has become crucial for modern cybersecurity frameworks. This technical article explores integrating AI technologies in security operations, focusing on practical applications in threat detection, automated response systems, and incident management. The article examines core components, including machine learning algorithms, behavioral analytics, and predictive security measures, while providing actionable insights for security professionals looking to develop expertise in AI-powered cybersecurity. By addressing both technical requirements and career development aspects, this article bridges traditional security practices and emerging AI technologies in the field. Key emphasis is placed on building practical skills, understanding system architectures, and implementing effective AI-driven security solutions while considering challenges such as data privacy, model accuracy, and regulatory compliance. The article encompasses current industry practices, emerging trends, and future developments in AI-enhanced security operations, making it valuable for practitioners and organizations transitioning to AI-integrated security frameworks.